Peningkatan Minat dan Hasil Belajar Ipa Melalui Penerapan Strategi Word Square Pada Siswa Kelas V Di SD Muhammadiyah 8 Jagalan Surakarta Tahun Ajaran 2015/2016 - Cahyono, Agung Budi; , Drs. Saring Marsudi, SH. M.Pd (2016)
This research applies learning strategies Word Square which aims to: 1) increase the interest of students of class V at SD Muhammadiyah 8 Jagalan Surakarta academic year 2015/2016, 2) improve learning outcomes Natural Sciences in Class V at SD Muhammadiyah 8 Jagalan Surakarta academic year 2015/2016. This research is a classroom action research. The subjects were students of class V at SD Muhammadiyah 8 Jagalan Surakarta totaling 29 students. Data collected through observation, interview, test and documentation. Data analysis technique used is interactive analysis starts from data reduction, data presentation and then draw conclusions. The results showed increased interest: 1) Interest pre-cycle student interest at 86.20% and 13.79% relatively less quite enough, 2) the first cycle of the first meeting of students has risen 6.89% interest, 3) the first cycle petemua II student interest 44.82 % 4) The second cycle of the first meeting of students has increased greatly interest 24.13%, 5) the second cycle II meeting the students really interest 89.65%. The results of the research study results showed: 1) the pre-test cycles less knowledgeable 27.58%, 55.17% perpengetahuan enough, 17.24% good knowledge, 2) the first cycle less knowledgeable 10.52%, 31.03% perpengetahuan enough , good knowledge 58.62%, 3.44% knowledgeable very good, 3) the second cycle shows, good knowledge 65.51%, 24.13% knowledgeable very good. The conclusion of this study were: 1) Word Square strategies can increase students' interest in class V at SD Muhammadiyah 8 Jagalan Surakarta, 2) Word Square strategies to improve learning outcomes Natural Sciences in Class V at SD Muhammadiyah 8 Jagalan Surakarta.